Natural Roosts Used By Bats In Central Amazonia, Brazil - Appel, Giulliana; Tavares, Valéria Da C.; Assis, Rafael Leandro de; Bobrowiec, Paulo Estefano Dineli (Mastozoologia Neotropical, 2021)
Some bat species use leaves or trees to roost during the day and the Stenodermatinae species are known to build tents in leaves of specific plant species. Tent-roosting bat species and Emballonuridae bats have a widespread geographic distribution in the Amazon region, but it can be difficult to find these bats perched in roosts due to changes in the availability of food and the low durability of the tents. Here, we describe the type of roost, tent architecture and plant species used by Uroderma bilobatum, Mesophylla macconnelli, and Saccopteryx leptura in a fragmented landscape in Brazilian Amazonia.
[Abrigos Naturais Usados Pelos Morcegos Na Amazônia Central, Brasil.]
Keywords: Phyllostomidae; Molossidae; Chiroptera